First report of transmissible gastroenteritis virus (TGEV) and porcine respiratory coronavirus (PRCV) in pigs from Poland - Marta Antas; Monika Olech (BMC Veterinary Research)
Abstract Porcine transmissible gastroenteritis virus (TGEV) and porcine respiratory coronavirus (PRCV) are swine coronaviruses belonging to the genus Alphacoronavirus in the family Coronaviridae. To date, there are no reports on the prevalence and genetic characterization of these viruses in domestic pigs from Poland. In this study, 828 serum samples were tested by TGEV/PRCV immunoassay to estimate TGEV and PRCV seroprevalence, while 277 nasal swabs and 221 stool samples were tested by real-time PCR to detect viral RNA. Our results revealed that 2.2% (95% CI 1.2, 3.2) of serum samples were positive for anti-TGEV antibodies, while 12.2% (95% CI 9.8, 14.4) of samples were positive for anti-PRCV antibodies. 2.5% (95% CI 1.5, 2.6) and 5.2% (95% CI 3.7, 6.7) of serum samples were inconclusive for TGEV and PRCV, respectively. RNA of TGEV was not detected in any of the tested samples, while PRCV RNA was detected in 6.22% of samples. Genetic and phylogenetic analysis revealed that all Polish PRCV strains were closely related to European and Korean PRCV strains than to American strains. Some of the Polish PRCV strains have a 672 nt deletion at the same position at the 5’ end of the S gene as other European and Korean PRCV strains, suggesting that they originated from the same precursor. Other Polish PRCV strains had a 690 nt deletion that differed in size and location from any of the known PRCV strains. This may suggest that these Polish PRCVs may have originated from different ancestor. Furthermore, the Polish PRCV strains showed some unique changes in their sequences, which may reflect their evolution. This study is the first report on the prevalence of TGEV/PRCV in pigs from Poland. In addition, this is the first report on the genetic characterization of Polish PRCV strains, which provide new information on PRCV heterogeneity.